Innovation Clusters : Combining Physical and Virtual Links - Brigitte Preissl (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Innovation is increasingly seen as a collective action which involves many different actors operating in a cluster context. These clusters are usually conceived as local agglomerations. In this paper it will be argued that they are an important tool to study innovation, but the globalisation of companies and markets and the specific requirements of innovation processes require the expansion of cluster concepts towards virtual dimensions. It will be shown that the combination of local and virtual cluster links improves access to essential resources in innovation. An examples taken from the automotive component sector will illustrate the concept.
Keywords: L62; L69; O32; 330; Innovation; cluster dynamics; automotive components; Innovation; Business Network; Regionale Konzentration; Virtuelles Unternehmen; Kraftfahrzeugzulieferer; Deutschland